RESPONS TANAMAN JAGUNGMANIS (Zea mays saccharataSturt)YANG DIBERIPUPUK GUANO DENGAN NPK DI LAHAN GAMBUT - Nainggolan, Gideon; Hapsoh, Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to determine the effect of fertilizer on crops and sweet corn crops on the provision of Guano fertilizer with NPK, and get the best dose of the treatment in peatland. The experiment was conducted in an experiment consisting of 5 treatments using a randomized block design. Each treatment has been repeated 4 times, so that 20 units of experiment are obtained. Each experimental unit consisted of 32 plants, 5 plants sampled. Individual treatment without fertilizer, guano fertilizer 6 Ton/ha + NPK 150 kg/ha, guano 6 Ton/ha + NPK 300 kg/ha, guano 12 Ton/ha + NPK 150 kg/ha, guano 12 Ton/ha + NPK 300 kg/ha. The data obtained were analyzed statistically and continued by using multiple Duncan multiple assay at 5% parameters observed were plant height, harvest age, tuna length, cob hemeters, cob weight with weight per plant, cob weight without weight per plant, Seeds per ear, cob production with per 6m2 weight, and unsweetened cob production per 6m2 of sweet corn. The result data showed better production of sweet corn plant obtained by Guano 12 Ton/ha with NPK 300 kg/ha.Keywords: Sweet Corn, Peat Land, Guano Fertilizer with NPK